Firm Characteristics and Corporate Governance Disclosure in Integrated Reports - Nicola Raimo; Marianna Zito; Alessandra Caragnano (Zbornik Radova Proceedings, 10th International Symposium on Natural Resources Management, 2020)
In recent years, the debate on corporate governance has considerably grown worldwide. In this scenario, corporate governance disclosure is gaining greater attention and the advent of integrated reporting offers a new interesting channel to companies for the dissemination of corporate governance information. This study aims at investigating the factors that can affect the level of corporate governance disclosure included in the integrated reports. Our analysis, conducted on a sample of 85 international companies shows that firm size and profitability positively influence the level of corporate governance disclosure. Moreover, it demonstrates a negative impact of CEO duality on corporate governance disclosure level.
Keywords: 330; Integrated reporting; Corporate governance; Disclosure; Corporate reporting; Firm characteristics